Eye-tracking multi-word units: some methodological questions - Carrol, Gareth; Conklin, Kathy (International Group for Eye Movement Research, 2015)
Eye-tracking in linguistics has focused mainly on reading at the level of the word or sentence. In this paper we discuss how the phenomenon of formulaic language might best be examined using this methodology. Formulaic language is fundamentally multi-word in nature, therefore an approach to eye-tracking that considers the “word” as the basic unit of analysis may require re-evaluation. We review the existing literature on single word and sentence processing, and also those studies that have used eye-tracking as a way of investigating formulaic language to date. We discuss how eye-tracking might elucidate the “added extra” processing advantage for formulaic language. We conclude with some suggestions about the best way to utilise eye-tracking within this sub-field of linguistic investigation.